Focal points in multiple threshold public goods games: A single-project meta-analysis - Luca Corazzini; Matteo M. Marini (Masaryk University, Faculty of Economics and Administration, 2022)
SThis paper is a single-project meta-analysis of four experiments that first model charitable giving as individual contributions to a multiplicity of competing threshold public goods. Given the centrality of the coordination dilemma as the number of recipients increases, we pool 15,936 observations at the individual level for the purpose of identi- fying the most effective focal points, their mechanics, and their implications for donors' wealth. We find that competition between public goods implies massive coordination problems that originate from fewer contributions and result in lower profits. In this setting, the most powerful coordination device turns out to be the existence of a single contribution option that stands out on its merits. We also observe an inverted U-shaped trend in the successful provision of public goods, offering evidence for experience as a focal point peculiar to the multiple-public-good framework. The effective focal points do not leverage greater contributions to solve the coordination dilemma, yet they generate higher earnings. Finally, delegation proves to be a sound device for reducing the risk of miscoordination as long as the delegate is formally obliged to pass along a high enough percentage of the transferred resources. We discuss possible implications of our findings.
Keywords: C90; C91; C92; H40; H41; L31; 330; meta-analysis; threshold public goods; charitable giving; fundraising; focal points